Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Publisher: Routledge _eprint: https://doi.org/10.1080/01436597.2018.1432351
Keywords: Amérique latine; Appropriation technologique; Social technology; Technologie sociale

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Marlei, Pozzebon; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
Number: 3 N'AVONS PAS ACCÈS
Keywords: Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Recherche; Technologie sociale; Transformations

Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Number: 9 Publisher: Routledge _eprint: https://doi.org/10.1080/01436597.2018.1432351
Keywords: Amérique latine; Libre accès; Social technology; Technologie sociale

Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Publisher: Routledge _eprint: https://doi.org/10.1080/01436597.2018.1432351
Keywords: Amérique latine; Libre accès; Social technology; Technologie sociale

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Pozzebon, Marlei; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
N'AVONS PAS ACCÈS
Keywords: Amérique centrale/sud; Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Nord / Sud; Recherche; Technologie sociale; Transformations